Influence of Vespa sp. Wasp Disturbance on Foraging Activities and Apis cerana Populations in the Greater Forest Park Area Ir. H. Juanda - Nuriyah, Syayidah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Honey bees (Apis spp.) play a crucial role in maintaining ecosystem balance through pollination, which directly impacts the sustainability of biodiversity and human food security. Studies on the antagonistic interactions between Apis cerana and Vespa sp. are still relatively limited in Indonesia, particularly in conservation areas such as Tahura Djuanda. This study aims to observe the disruptive factors of Vespa sp. wasps, a natural enemy of the Apis cerana honey bee in Tahura Djuanda. The methods used were direct field observation and recording of Vespa sp. activity on bee colonies. The seven-day study showed that disruption by Vespa sp. wasps on the foraging activity of Apis cerana bees occurred with high frequency. The average number of Vespa sp. presence per day in insect tubes installed in calliandra flowers reached 23,28 individuals, significantly higher than the control of 3,43 individuals per day. This disturbance caused a significant decrease in bee foraging activity, increased defensive behavior, and the potential for colonies to abandon the nest (absconding). This study confirms that Vespa sp. is a natural enemy that can reduce the activity and productivity of Apis cerana colonies, and that control strategies are needed to minimize its impact.